2007
DOI: 10.1007/s11270-007-9583-x
|View full text |Cite
|
Sign up to set email alerts
|

Hydrochemistry of Arsenic-Enriched Aquifer from Rural West Bengal, India: A Study of the Arsenic Exposure and Mitigation Option

Abstract: The present study aims to understand the hydrochemistry vis-à-vis As-exposure from drinking groundwater in rural Bengal. The characteristic feature of the groundwaters are low Eh (range, −151 to −37 mV; mean, −68 mV) and nitrate (range, 0.01-1.7 mg/l; mean, 0.14 mg/l) followed by high alkalinity (range, 100-630 mg/l; mean, 301 mg/l), Fe (range, 0.99-38 mg/l; mean, 8.1 mg/l), phosphate (range, 0.01-15 mg/l; mean, 0.54 mg/l), hardness (range, 46-600 mg/l; mean, 245 mg/l) and sulphate (range, 0.19-88 mg/l; mean, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(26 citation statements)
references
References 49 publications
3
18
0
Order By: Relevance
“…Similar levels of As in groundwater (159 μg l −1 in average) were reported from the Hanoi area, where 72% of the tube wells contained As levels higher than 10 μg l −1 (Berg et al 2001). Comparable levels of As contamination were observed in Bangladesh, India, and Taiwan (Chowdhury et al 2000;Nath et al 2008;Wang et al 2007). We detected much lower As levels in the groundwater at sites close to the Red River than at sites located on the banks of the Chau Giang River; this has also been observed by .…”
Section: Arsenic Concentration In Groundwatersupporting
confidence: 69%
See 1 more Smart Citation
“…Similar levels of As in groundwater (159 μg l −1 in average) were reported from the Hanoi area, where 72% of the tube wells contained As levels higher than 10 μg l −1 (Berg et al 2001). Comparable levels of As contamination were observed in Bangladesh, India, and Taiwan (Chowdhury et al 2000;Nath et al 2008;Wang et al 2007). We detected much lower As levels in the groundwater at sites close to the Red River than at sites located on the banks of the Chau Giang River; this has also been observed by .…”
Section: Arsenic Concentration In Groundwatersupporting
confidence: 69%
“…On the other hand, compared to the data obtained in this study, higher levels of sulfate and slightly lower Fe concentrations in the groundwater were reported from the Mekong Delta, southern Vietnam, where acid, sulfaterich soils are abundant (Nguyen and Itoi 2009). Moreover, the chemical features of the groundwater observed in the present study are quite similar to those in Bangladesh and West Bengal, India (Nickson et al 2000;Anawar et al 2003;Nath et al 2008). Occurrence of As in aquifer sediments…”
Section: Arsenic Concentration In Groundwatersupporting
confidence: 64%
“…Biswas et al [151] also reported lower As concentrations in hair and nail samples from children compared with adults in the Samta village of Bangladesh. Nath et al [152] reported similar findings in their study population of Baruipur, South 24 Parganas district, West Bengal. Medical screening in the Bangladesh region [153] showed that most of the study populations were affected by keratosis and melanosis, whereas a few subjects were affected by chronic bronchitis and whole-body infection.…”
Section: Bangladesh and West Bengal (India)supporting
confidence: 62%
“…Several workers have reported methane in the aquifers from many parts of the basin [38,122]. The bicarbonate may also be supplied from local biogeochemical processes to the groundwater system [123,124]. Several workers reported strong to moderate correlation between arsenic and iron which indicates the release of arsenic due to dissolution of and desorption from iron hydroxides in the sediments [117,120].…”
Section: Biogeochemical Redox Transformationmentioning
confidence: 99%